Pengaruh Tingkat Pengetahuan, Kualitas Layanan, Sosialisasi Produk Dan Literasi Nasabah Terhadap Eksistensi Bank Syariah Indonesia (BSI) di Tapanuli Tengah - Sri Wulandari Bugis; Tuti Anggraini (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the effect of Knowledge Level, Service Quality, Product Socialization and Customer Literacy Level both partially and simultaneously on the Existence of Bank Syariah Indonesia (BSI) in Central Tapanuli. This research is a type of quantitative research with a causal associative approach. The population in this study is the Muslim community that uses Islamic banking products in Central Tapanuli. The research sample is 100 people using purposive sampling method. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that the level of knowledge, service quality, product socialization and customer literacy level had a positive and significant effect on the existence of Bank Syariah Indonesia (BSI) in Central Tapanuli either partially or simultaneously.